Discrete-time event-triggered higher order sliding mode control for consensus of 2-DOF robotic arms. (November 2020) - Patel, Keyurkumar; Mehta, Axaykumar
Abstract: This paper proposes a discrete-time event-triggered higher-order sliding mode protocol for the leader-following consensus of Discrete Homogeneous Multi-Agent Systems (DHMAS). The discrete version of the Super-Twisting Algorithm (DSTA) which is one of the most popular algorithm of higher order sliding mode control blended with event-triggered control approach is used to design the protocol. The DSTA algorithm is robust against the uncertainties present in the DHMAS and improve the consensus performance. The event-triggered control approach reduces the usage of power and communication resources due to the intermittent communication with the neighboring agents to achieve consensus. For implementing the proposed consensus protocol, each follower agent of DHMAS monitor for the event-triggering condition as defined in this paper. The sufficient condition for global stability with proposed consensus protocol is also derived to ensure the stable operation of DHMAS. Further, the proposed protocol is implemented on a discrete homogeneous multi-agent system set up comprise of 2-DOF flexible joint robotic arm considering one robotic arm as a leader and others as followers to show the efficacy of the proposed protocol.